2008
DOI: 10.1111/j.1553-2712.2008.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Multicenter Bronchiolitis Study: Predicting Intensive Care Unit Admissions

Abstract: Objectives: The authors sought to identify predictors of intensive care unit (ICU) admission among children hospitalized with bronchiolitis for ‡24 hours. Methods:The authors conducted a prospective cohort study during two consecutive bronchiolitis seasons, 2004 through 2006, in 30 U.S. emergency departments (EDs). All included patients were aged <2 years and had a final diagnosis of bronchiolitis. Regular floor versus ICU admissions were compared.Results: Of 1,456 enrolled patients, 533 (37%) were admitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
74
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 45 publications
10
74
1
5
Order By: Relevance
“…Although a prior bronchiolitis-related study reported that Hispanic children had a longer ED length of stay (LOS) than non-Hispanic white (NHW) and non-Hispanic black (NHB) children, 14 other studies concluded that race/ethnicity were not predictors of intensive care unit (ICU) admission or unscheduled healthcare visits post-ED discharge. 15,16 Determining if race/ethnicity is independently associated with certain bronchiolitis management tendencies has implications from both a health disparities standpoint (ie, unequal care based on race/ethnicity) and from a clinical perspective (ie, the potential of certain practices, such as clinical pathways, to increase the likelihood of equitable treatment). To address this knowledge gap, we examined prospective data from a multicenter study designed to evaluate multiple factors related to bronchiolitis hospitalization.…”
mentioning
confidence: 99%
“…Although a prior bronchiolitis-related study reported that Hispanic children had a longer ED length of stay (LOS) than non-Hispanic white (NHW) and non-Hispanic black (NHB) children, 14 other studies concluded that race/ethnicity were not predictors of intensive care unit (ICU) admission or unscheduled healthcare visits post-ED discharge. 15,16 Determining if race/ethnicity is independently associated with certain bronchiolitis management tendencies has implications from both a health disparities standpoint (ie, unequal care based on race/ethnicity) and from a clinical perspective (ie, the potential of certain practices, such as clinical pathways, to increase the likelihood of equitable treatment). To address this knowledge gap, we examined prospective data from a multicenter study designed to evaluate multiple factors related to bronchiolitis hospitalization.…”
mentioning
confidence: 99%
“…Much existing work on predictive modeling for bronchiolitis, such as Parker et al [2,21,[29][30][31]42], starts from univariate logistic regression to identify useful predictors. This approach may miss an opportunity to identify combinations of predictors that together have good predictive power, when each individual predictor has little or no predictive power by itself [263].…”
Section: Using Machine Learning Methodsmentioning
confidence: 99%
“…For children with bronchiolitis in the ED, Damore et al [29] identified several predictors of ICU admission and built a logistic regression model to predict ICU admission, with an AUC of 80%. This study excluded bronchiolitis patients with previous ED visits.…”
Section: Predicting Icu Admissionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] 최근 감염된 바이러스 종류 및 바이러스 아형에 따라 중 증도가 다르게 나타나고 2,3) 특히 중복 감염이 중증도에 상당 한 영향을 미친다는 보고가 있으며, 4,5) 아토피 가족력이나 [13][14][15][16] 환아의 아토피 소견 15) 및 간접 흡연이 [17][18][19] 중증 세기관 지염과 관련이 있다는 보고도 있다 그러나 일부에서는 세기 .…”
unclassified